Agriculture, natural resource management, and “development” beyond the biophysical - German, L.; Verma, R.; Ramisch, Joshua J. (Springer, 2010)
Knowledge, culture, and relations of power shape the institutionalized discourses, ideologies, and practices of “development” as well as the everyday natural resource management practices of women and men around the world. As a result, a broader and interdisciplinary perspective on agriculture, natural resource management, and development practice beyond purely biophysical approaches is urgently needed. This chapter – like the volume it introduces – offers insights into the socio-cultural, political-economic, and environmental effects of development (and their very real implications for women and men in the global South), highlighting the challenges and “mis-adventures” associated with past and current development approaches and practices. It also presents strands of theory that can help to make sense of these realities, and provides concrete recommendations for moving beyond them. The volume’s case studies, introduced in this chapter, demonstrate the possibility and necessity of reaching out beyond the borders of anthropological and social scientific disciplines in ways that are meaningful and valuable to others. The case studies also articulate the challenges faced by sociocultural scientists working in arenas dominated by other disciplines. The chapter argues for the importance of rigorous social science, and for understanding the dynamics of knowledge, culture, and power in diverse contexts. At the same time, it highlights the need to move beyond critique of interdisciplinary ventures towards constructive engagement with other disciplines, and makes a case for the unique contributions social science can make to agriculture makes natural resource management.